Eco-Control and Its Dual Impact on Environmental and Economic Performance - Muhammad Try Dharsana; Andi Iqra Pradipta Natsir; Naufal Muhammad Aksah; Ihya' Ulumuddin (Hasanuddin Economics and Business Review, 2024)
This study examines the dual impact of eco-control on both environmental and economic performance in the manufacturing sector. Drawing on data from 183 managers of manufacturing companies in Indonesia, this research employs Partial Least Squares Structural Equation Modelling (PLS-SEM) to analyse the relationships between eco-control, environmental performance, and economic performance. The findings reveal that eco-control significantly enhances environmental performance, which in turn positively influences economic outcomes. Additionally, eco-control has a direct positive effect on economic performance, suggesting that firms with robust eco-control mechanisms are more likely to achieve greater operational efficiency and financial success. The mediation analysis further confirms that environmental performance plays a crucial role in transmitting the positive effects of eco-control to economic performance. These results contribute to the growing body of literature on sustainability and corporate strategy by demonstrating the value of integrating eco-control systems to achieve both environmental and economic objectives. The study also highlights the importance of eco-control in aligning corporate sustainability initiatives with long-term profitability, particularly in sectors with high environmental impact. Limitations and directions for future research are discussed, including the need for broader studies across different industries and regions.